Scoping review: a relevant methodological approach for knowledge synthesis in Brazil’s health literature - Barbosa Filho, Valter Cordeiro (2019)
A methodologically robust approach to synthesize relevant knowledge in health literature is the scoping review, which is used to answer broader questions (e.g., “What is known about this concept?”) and can be used to map evidence for research and practice decision-making. This paper discussed the importance of scoping reviews as a methodological approach for knowledge synthesis in Brazil’s health literature. Definitions and methodological steps were discussed. We examined 45 scoping reviews that were published in Brazil’s journals or available as thesis or dissertations to discuss their content and methodological characteristics. Recommendations for authors were presented in order to improve the planning, executing and reporting of further scoping reviews in Brazil. This will help Brazilian researchers and health professionals to understand when and how scoping reviews can be helpful for knowledge synthesis on health topics, including for physical activity and health research area.